A Development of a Project Basedo Student Work Base Learning on Electrical Lighting Installation in Smk Negeri 2 Lubuk Basung - Alan Surya Pratama; Ridwan Ridwan; Hansi Effendi (Postgraduate School, Universitas Negeri Padang, 2019)
This research aims to: (1) develop learner worksheets lesson installation of electric lighting and (2) to describe the response of teachers on implementation-based learning, project based learning on subjects of installation of lighting electricity. This research is a research and development (R&D) and ADDIE model. This stage of the analysis is the process that will determine the learning process that will be studied learners. The stage design was developed from the initial draft of the learning process and assessment instruments. The stage of development is based on the initial draft of the repair validation expert lecturers and teachers, then conducted a limited trial in SMK Negeri 2 Lubuk Basung. Stage of implementation of the testing results of tests done learning learners and test project to find out the effectiveness of learner worksheets developed. This stage is also done charging the response question form filled out by teachers and learners. the last stage is evaluation, which the researchers evaluate at each phase of the development of learning materials worksheet learners further revision to find out if learning materials developed for already applied or Yet in learning. Data capture instrument in the research on learner worksheets, now the response of teachers and learners. Validity of data analysis techniques and materials now response using category scale of four. The results showed that in the aspect of validation, a worksheet developed learners have the average percentage in the valid criteria with the percentage of 83.33%. Aspects of the practicalities, learner worksheets developed have the average percentage in the practical value of the percentage criterion 88.64%. The aspect of effectiveness, the learner worksheets developed in criteria effective percentage that has good value knowledge 76.15% nor the project measured from the ketuntasan of classical learning to learners. The conclusion to be drawn that the learner worksheets based project based learning on subjects of installation of electric lighting already fits the criteria of a valid, practical and effective to use.